Preparation method of anti-corrosion heat dissipation coating, anti-corrosion heat dissipation coating and battery

By spraying or rolling the anti-corrosion heat dissipation coating prepared by spraying or rolling the lithium-ion battery case, the shortcomings in battery heat dissipation and energy density are solved, and better heat dissipation performance and battery energy density are achieved.

CN119505634APending Publication Date: 2025-02-25SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411639563.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in terms of heat dissipation and energy density, especially the internal corrosion and external heat dissipation effects of the aluminum shell, which leads to poor heat dissipation performance of the battery cell.

Method used

An anti-corrosion and heat dissipation coating is used to prepare an anti-corrosion and heat dissipation coating, including configuring a mixture liquid and preparing an anti-corrosion and heat dissipation coating through ultrasonic dissipation, heating and stirring, and spraying or rolling on the inner and outer side walls of the battery case.

Benefits of technology

The corrosion-resistant heat dissipation coating less than 0.1mm is formed, which significantly improves the heat dissipation ability and energy density of the battery cell, and avoids the internal corrosion problem of the aluminum shell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505634A_ABST
    Figure CN119505634A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-corrosion heat dissipation coating, the anti-corrosion heat dissipation coating and a battery, the preparation method of the anti-corrosion heat dissipation coating comprises the following steps: preparing a mixed solution, the mixed solution comprises, by mass, 10%-20% of a curing agent, 1.5%-3% of a dispersant, 1.5%-3% of an antifoaming agent, 3%-10% of an additive, 0%-3% of an auxiliary agent and 61%-84% of a solvent; performing ultrasonic dispersion on the mixed solution for 3-4 hours; adding 10%-20% of film-forming resin, and raising the temperature to 70 DEG C-80 DEG C; stirring for 5-6 hours at a constant temperature, and cooling to obtain the anti-corrosion heat dissipation coating. The invention also discloses a battery using the anti-corrosion heat dissipation coating prepared by the preparation method. The anti-corrosion heat dissipation coating prepared by the preparation method is sprayed or roller-coated on the inner and outer side walls of a shell and a cover body of a battery, so that the heat dissipation capability and the energy density of a battery cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an anti-corrosion heat dissipation coating, the anti-corrosion heat dissipation coating and a battery. Background Art

[0002] As the size and capacity of battery cells increase, the heat dissipation problem needs to be solved urgently. The existing square shell battery cells are usually insulated by wrapping the aluminum shell with a blue film and pasting an insulating sheet on the top cover. The insulating sheet is made of PET, which has a low thermal conductivity and poor heat dissipation performance. As the capacity of the battery cell increases, this effect will increase exponentially. A small number of them are coated with a coating similar to car paint, which is too thick and seriously affects the energy density of the battery cell.

[0003] The aluminum shell also has internal corrosion problems. The heat dissipation effect is poor because the outside is glued. The top cover uses a top patch, which also leads to poor heat dissipation. Summary of the invention

[0004] In order to overcome the defects in the prior art, the present invention provides a method for preparing an anti-corrosion heat dissipation coating, an anti-corrosion heat dissipation coating and a battery. The anti-corrosion heat dissipation coating prepared by the preparation method is sprayed or rolled on the inner and outer walls of the battery shell, which can improve the heat dissipation capacity of the battery cell and the energy density of the battery cell.

[0005] To achieve the above object, the technical solution adopted by the present invention is a method for preparing an anti-corrosion heat dissipation coating, comprising the following process:

[0006] Prepare a mixed solution, the mixed solution includes 10% to 20% by weight of a curing agent, 1.5% to 3% by weight of a dispersant,

[0007] 1.5% to 3% defoamer, 3% to 10% additive, 0% to 3% auxiliary agent and 61% to 84% solvent;

[0008] Ultrasonic dispersion of the mixed solution for 3 h to 4 h;

[0009] Adding a film-forming resin accounting for 10% to 20% of the mass of the mixed solution, and heating the mixed solution to 70° C. to 80° C. using a heating device;

[0010] The mixture is stirred for 5 to 6 hours and cooled to room temperature to obtain the anti-corrosion heat dissipation coating.

[0011] Wherein, the room temperature is 28°C to 32°C.

[0012] The anti-corrosion heat dissipation coating is prepared by the above scheme, which is used for spraying or roller coating on the inner and outer walls of the battery shell to achieve the purpose of insulation and heat dissipation. In the traditional method, a blue film is used on the outside of the battery shell, and an insulating sheet is used on the top cover. The insulating sheet is made of PET material, has a small thermal conductivity, and has poor heat dissipation performance. As the capacity of the battery cell increases, the heat dissipation problem caused by poor heat dissipation capacity becomes more and more serious. The anti-corrosion heat dissipation coating prepared by the method disclosed in the present application can form an anti-corrosion heat dissipation coating less than 0.1mm on the inner and outer walls of the battery shell, thereby improving the heat dissipation capacity of the battery cell. At the same time, the coating thickness is much smaller than the thickness of the blue film and the insulating sheet, which improves the energy density of the battery cell.

[0013] Furthermore, the curing agent is preferably an acid anhydride curing agent, and the acid anhydride curing agent includes phthalic anhydride.

[0014] Furthermore, the dispersant is preferably a hydrophobic dispersant, and the hydrophobic dispersant includes a fatty acid salt.

[0015] Furthermore, the defoaming agent includes polydimethylsiloxane.

[0016] Furthermore, the additive includes one or both of porous nano-silicon dioxide and silicon carbide.

[0017] Furthermore, the auxiliary agent includes aluminum hydroxide.

[0018] Furthermore, the solvent includes one or a mixture of two or more of ethanol, acetone or ethyl acetate.

[0019] Furthermore, the film-forming resin includes one or both of modified epoxy resin and silicone resin, and the modified epoxy resin accounts for 10% to 20% of the mass of the mixed liquid, and the silicone resin accounts for 10% to 15% of the mass of the mixed liquid.

[0020] Further, the step of stirring for 5h to 6h comprises:

[0021] The mixture was stirred with a magnetic stirrer at a rotation speed of 180 r / min.

[0022] Furthermore, the additives also include solid fillers. The solid fillers, such as silicon powder, can increase the thermal conductivity of the anti-corrosion heat dissipation coating.

[0023] An anti-corrosion heat dissipation coating is prepared using the above-mentioned anti-corrosion heat dissipation coating preparation method.

[0024] A battery comprises a shell and a cover, wherein at least the inner wall and / or the outer wall of the shell and / or the cover are coated with the above-mentioned anti-corrosion heat dissipation coating.

[0025] Furthermore, the anti-corrosion heat dissipation coating of the inner wall of the shell and the cover body uses an anti-corrosion heat dissipation coating with solid fillers added. When the battery reacts to supply power, the internal heat is higher than the outside, so the inside of the battery needs a stronger heat dissipation capacity, and adding solid fillers can increase the heat dissipation capacity.

[0026] Furthermore, the anti-corrosion heat dissipation coating is provided on the inner side walls of the shell and the cover by spraying.

[0027] Furthermore, the outer side walls of the shell and the cover are provided with the anti-corrosion heat dissipation coating by roller coating.

[0028] Furthermore, the thickness of the anti-corrosion heat dissipation coating is less than 0.1 mm.

[0029] By means of the above technical solution, the beneficial effects of the present invention are as follows:

[0030] 1. In the traditional method, a blue film is used on the outside of the battery shell and an insulating sheet is used on the top cover. The insulating sheet is made of PET material, has a low thermal conductivity, and has poor heat dissipation performance. As the capacity of the battery cell increases, the heat dissipation problem caused by poor heat dissipation capacity becomes more serious. The anti-corrosion heat dissipation coating prepared by the method disclosed in the present application can form an anti-corrosion heat dissipation coating less than 0.1 mm on the inner and outer walls of the battery shell, thereby improving the heat dissipation capacity of the battery cell. At the same time, the coating thickness is much smaller than the thickness of the blue film and the insulating sheet, thereby improving the energy density of the battery cell.

[0031] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is a flow chart of a method for preparing an anti-corrosion heat dissipation coating according to an embodiment of the present invention;

[0034] Figure 2 Schematic diagram of a battery housing in an embodiment of the present invention.

[0035] The figure markings of the above figures are: 1. large surface; 2. side surface; 3. positive pole; 4. negative pole. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0037] It should be noted that, in the description of the present invention, the terms "first", "second", etc. are only used for descriptive purposes and to distinguish similar objects. There is no order of precedence between the two, and they cannot be understood as indicating or implying relative importance. In addition, in the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0038] Combination Figure 1-2 As shown, the present invention discloses a method for preparing an anti-corrosion heat dissipation coating, comprising the following process:

[0039] A mixed solution is prepared, wherein the mixed solution comprises:

[0040] 10% to 20% of a curing agent, wherein the curing agent is preferably an anhydride curing agent, such as phthalic anhydride;

[0041] 1.5% to 3% of a dispersant, wherein the dispersant is preferably a hydrophobic dispersant, such as a fatty acid salt;

[0042] 1.5% to 3% of a defoaming agent, wherein the defoaming agent comprises polydimethylsiloxane;

[0043] 3% to 10% of an additive, wherein the additive is preferably a component with high thermal conductivity, such as one or both of porous nano-silicon dioxide and silicon carbide;

[0044] 0% to 3% of an auxiliary agent, wherein the auxiliary agent includes a flame retardant aluminum hydroxide;

[0045] 61% to 84% of a solvent, wherein the solvent comprises one or a mixture of two or more of ethanol, acetone or ethyl acetate.

[0046] Optionally, the additive includes a solid filler. The anti-corrosion heat dissipation coating prepared by the above anti-corrosion heat dissipation coating preparation method can be used to coat the inner wall of the battery housing. When the battery reaction is powered, the heat is mainly concentrated in the battery housing, so the inner side of the battery needs a stronger heat dissipation capacity. Adding a solid filler with high thermal conductivity such as silicon powder can increase the heat dissipation capacity.

[0047] Use an ultrasonic disperser to ultrasonically disperse the mixed liquid for 3h to 4h. The ultrasonic disperser is a precision device that uses the shear force and shear effect generated by ultrasonic vibration to achieve the purpose of material dispersion, emulsification, mixing, etc. Its mechanism of action is: when the ultrasonic beam passes through the material, high-frequency vibrations will be generated inside the material, and cavitation bubbles and gas-liquid interfaces of varying sizes will also be formed. These bubbles and interfaces will quickly form, expand, collapse and explode, producing strong impact, vibration and eddy current effects. These effects can break the entanglement and electrostatic force on the surface of the material, disperse the material, and make the dispersion effect more uniform, thereby achieving the purpose of dispersion, emulsification and mixing. The coating after ultrasonic dispersion treatment has higher dispersibility and stability.

[0048] Add a film-forming resin accounting for 10% to 20% of the mass of the mixed liquid, and use a heating device to heat the mixed liquid to 70°C to 80°C. Film-forming resin refers to the ability to adhere to substances to form a film, and is therefore the basis of the coating. It determines the basic properties of the coating, and mainly includes oils and resins, and also includes some non-volatile active diluents. Polymer resins or oils are the main film-forming resins of coatings and are indispensable in any coating. In the present application, the film-forming resin includes one or both of modified epoxy resins or silicone resins, and the modified epoxy resin accounts for 10% to 20% of the mass of the mixed liquid, and the silicone resin accounts for 10% to 15% of the mass of the mixed liquid.

[0049] The mixed solution was stirred at a constant temperature of 180 r / min using a magnetic stirrer for 5 to 6 hours, and the anti-corrosion heat dissipation coating was obtained after cooling to room temperature.

[0050] The anti-corrosion heat dissipation coating is prepared by the above scheme, which is used for spraying or roller coating on the inner and outer walls of the battery shell to achieve the purpose of insulation and heat dissipation. In the traditional method, a blue film is used on the outside of the battery shell, and an insulating sheet is used on the top cover. The insulating sheet is made of PET material, has a small thermal conductivity, and has poor heat dissipation performance. As the capacity of the battery cell increases, the heat dissipation problem caused by poor heat dissipation capacity becomes more and more serious. The anti-corrosion heat dissipation coating prepared by the method disclosed in the present application can form an anti-corrosion heat dissipation coating less than 0.1mm on the inner and outer walls of the battery shell, thereby improving the heat dissipation capacity of the battery cell. At the same time, the coating thickness is much smaller than the thickness of the blue film and the insulating sheet, which improves the energy density of the battery cell.

[0051] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described in detail. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] In Example 1, the prepared mixed solution includes 10% by weight of phthalic anhydride, 1.5% by weight of fatty acid salt, 1.5% by weight of polydimethylsiloxane, 3% by weight of porous nano-silica and 84% by weight of ethanol.

[0053] After the mixed solution was stirred uniformly, an ultrasonic disperser was used to ultrasonically disperse the mixed solution for 3 hours.

[0054] Add 10% by weight of modified epoxy resin to the mixed solution after ultrasonic dispersion, and heat the mixed solution to 70° C. by a heating device.

[0055] The mixture was stirred at a constant temperature of 70°C for 5 h using a magnetic stirrer at a speed of 180 r / min.

[0056] The mixed liquid is cooled to room temperature to obtain an anti-corrosion heat dissipation coating a.

[0057] In Example 2, the prepared mixed solution includes 15% by weight of phthalic anhydride, 3% by weight of fatty acid salt, 3% by weight of polydimethylsiloxane, 10% by weight of silicon carbide, 3% by weight of aluminum hydroxide and 66% by weight of acetone.

[0058] After the mixed solution was stirred uniformly, an ultrasonic disperser was used to ultrasonically disperse the mixed solution for 4 hours.

[0059] Add 15% of the mass of organic silicon resin into the mixed solution after ultrasonic dispersion, and heat the mixed solution with modified epoxy resin to 80° C. by a heating device.

[0060] The mixture was stirred at a constant temperature of 80°C for 6 h using a magnetic stirrer at a speed of 180 r / min.

[0061] After the mixed liquid is cooled to room temperature, the anti-corrosion heat dissipation coating b is obtained.

[0062] Example 3: The prepared mixed solution includes 12% by weight of phthalic anhydride, 2% by weight of fatty acid salt, 2% by weight of polydimethylsiloxane, 4% by weight of porous nano-silicon dioxide, 4% by weight of silicon carbide, 1% by weight of silicon micropowder, 1.5% by weight of aluminum hydroxide and 73.5% by weight of ethyl acetate.

[0063] After the mixed solution was stirred uniformly, an ultrasonic disperser was used to ultrasonically disperse the mixed solution for 3.5 hours.

[0064] Add 20% of the mass of modified epoxy resin to the mixed solution after ultrasonic dispersion, and heat the mixed solution to 75° C. by a heating device.

[0065] The temperature was kept constant at 75°C and the mixture was stirred at 180 r / min using a magnetic stirrer for 5.5 h.

[0066] After the mixed liquid is cooled to room temperature, an anti-corrosion heat dissipation coating c is obtained.

[0067] Example 4: The prepared mixed solution includes 13% by weight of phthalic anhydride, 2.5% by weight of fatty acid salt, 2.5% by weight of polydimethylsiloxane, 2% by weight of porous nano-silica, 1% by weight of silicon powder, 1% by weight of aluminum hydroxide, 34% by weight of ethanol and 44% by weight of acetone.

[0068] After the mixed solution was stirred uniformly, an ultrasonic disperser was used to ultrasonically disperse the mixed solution for 3.2 hours.

[0069] Add 10% by weight of organic silicon resin to the mixed solution after ultrasonic dispersion, and heat the mixed solution to which the modified epoxy resin is added to 77° C. by a heating device.

[0070] The temperature was kept constant at 77°C and the mixture was stirred at 180 r / min using a magnetic stirrer for 5.2 h.

[0071] After the mixed liquid is cooled to room temperature, the anti-corrosion heat dissipation coating d is obtained.

[0072] Example 5: The prepared mixed solution includes 14% by weight of phthalic anhydride, 2.8% by weight of fatty acid salt, 2.2% by weight of polydimethylsiloxane, 2% by weight of porous nano-silicon dioxide, 1% by weight of silicon carbide, 2% by weight of silicon micropowder, 2% by weight of aluminum hydroxide, 25% by weight of ethanol, 25% by weight of acetone and 24% by weight of ethyl acetate.

[0073] After the mixed solution was stirred uniformly, an ultrasonic disperser was used to ultrasonically disperse the mixed solution for 3.6 hours.

[0074] Add 10% of the mixed liquid by weight of organic silicon resin and 10% of the mixed liquid by weight of modified epoxy resin to the mixed liquid after ultrasonic dispersion, and heat the mixed liquid to which the modified epoxy resin is added to 73° C. by a heating device.

[0075] The temperature was kept constant at 73°C and the mixture was stirred at 180 r / min using a magnetic stirrer for 5.7 h.

[0076] After the mixed liquid is cooled to room temperature, the anti-corrosion heat dissipation coating e is obtained.

[0077] The ingredients in the mixed solution in Examples 1 to 5 are shown in the following table:

[0078]

[0079]

[0080] The present application also discloses a battery, comprising a shell and a cover, wherein the inner and outer walls of the shell and the cover are coated with the above-mentioned anti-corrosion heat dissipation coating, and the thickness of the anti-corrosion heat dissipation coating is less than 0.1 mm.

[0081] The inner sidewalls of the shell and the cover are provided with the anti-corrosion heat dissipation coating by spraying, and the outer sidewalls of the shell and the cover are provided with the anti-corrosion heat dissipation coating by roller coating.

[0082] Optionally, the anti-corrosion heat dissipation coating of the inner wall of the shell and the cover body uses an anti-corrosion heat dissipation coating with solid fillers added. When the battery reacts to supply power, the heat is mainly concentrated in the battery shell, so the inside of the battery needs a stronger heat dissipation capacity, and adding solid fillers with high thermal conductivity such as silicon powder can increase the heat dissipation capacity.

[0083] The following experiments verify that the heat dissipation effect of the battery disclosed in this application is better:

[0084] Take five of the above batteries, and respectively coat the five batteries with anti-corrosion heat dissipation coating a, anti-corrosion heat dissipation coating b, anti-corrosion heat dissipation coating c, anti-corrosion heat dissipation coating d, and anti-corrosion heat dissipation coating e.

[0085] Among them, three temperature sensing lines T1, T2 and T3 are set at equal intervals at the center of the large surface 1 of the battery shell, a temperature sensing line is set at the center of the side surface 2 of the battery shell, and a temperature sensing line is set on each of the positive electrode column 3 and the negative electrode column 4 of the battery.

[0086] The conventional blue film battery was selected as a comparative example. The temperature of each temperature sensing line on the battery was tested at different discharge rates.

[0087] The test results are as follows:

[0088] 1. 0.5 times discharge rate:

[0089]

[0090]

[0091] 2. 1x discharge rate:

[0092]

[0093]

[0094] It can be seen from the experimental results that at the same discharge rate, the temperature of the battery coated with the anti-corrosion heat dissipation coating disclosed in this application is 1°C to 2°C lower than that of the blue film battery on average. Therefore, the anti-corrosion heat dissipation coating prepared by the anti-corrosion heat dissipation coating preparation method disclosed in this application forms an anti-corrosion heat dissipation coating on the battery shell, which has a better heat dissipation effect than the traditional blue film method.

[0095] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing an anti-corrosion heat dissipation coating, characterized in that: The following processes are included: Prepare a mixed liquid, the mixed liquid comprising 10% to 20% of a curing agent, 1.5% to 3% of a dispersant, 1.5% to 3% of a defoaming agent, 3% to 10% of an additive, 0% to 3% of an auxiliary agent and 61% to 84% of a solvent in a mass ratio; Ultrasonic dispersion of the mixed solution for 3 h to 4 h; Adding a film-forming resin accounting for 10% to 20% of the mass of the mixed solution, and heating the mixture to 70° C. to 80° C.; The mixture is stirred for 5 to 6 hours and cooled to room temperature to obtain the anti-corrosion heat dissipation coating.

2. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The curing agent includes phthalic anhydride.

3. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The dispersant includes a fatty acid salt.

4. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The defoaming agent includes polydimethylsiloxane.

5. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The additive includes one or both of porous nano-silicon dioxide and silicon carbide.

6. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The auxiliary agent includes flame retardant aluminum hydroxide.

7. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The solvent includes one or a mixture of two or more of ethanol, acetone or ethyl acetate.

8. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The film-forming resin includes one or both of modified epoxy resin and silicone resin, and the modified epoxy resin accounts for 10% to 20% of the mass of the mixed liquid, and the silicone resin accounts for 10% to 15% of the mass of the mixed liquid.

9. The method for preparing the anti-corrosion heat dissipation coating according to claim 1, characterized in that: The step of stirring for 5h to 6h comprises: The mixed solution was stirred at a constant temperature using a magnetic stirrer at a speed of 180 r / min.

10. The method for preparing the anti-corrosion heat dissipation coating according to claim 5, characterized in that: The additives also include solid fillers.

11. An anti-corrosion heat dissipation coating, characterized in that: The anti-corrosion heat dissipation coating is prepared using the anti-corrosion heat dissipation coating preparation method described in any one of claims 1-10.

12. A battery, characterized in that: It comprises a shell and a cover, wherein at least the inner wall and / or the outer wall of the shell and / or the cover are coated with the anti-corrosion heat dissipation coating according to claim 13.

Citation Information

Patent Citations

  • Insulating and heat-radiating coating composition, and insulating and heat-radiating product implemented therewith

    CN109563361A